Improving Family Functioning with Social Skills Training: Evidence from a Quasi-Experimental Study - Saadati, Nadereh; Yousefi, Zahra (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: To examine the effectiveness of social skills training on enhancing family functioning among married individuals.Methods and Materials: Employing a quasi-experimental design, this study involved 30 married individuals visiting a private counseling center, divided equally into experimental and control groups. The experimental group received an 8-week social skills training program focused on improving communication, problem-solving, and emotional regulation within marital relationships.Findings: Results indicated significant improvements in family functioning scores for the experimental group, as compared to the control group, both immediately following the intervention and at a 3-month follow-up. The analysis of variance with repeated measurements underscored the positive impact of social skills training on enhancing family dynamics.Conclusion: Social skills training emerges as a viable intervention for improving family functioning among married couples, suggesting its potential inclusion in marital counseling services to foster healthier family relationships.